The characteristics of 76 atypical neurofibromas as precursors to neurofibromatosis 1 associated malignant peripheral nerve sheath tumors. Issue 6 (2nd February 2018) - Higham, Christine S; Dombi, Eva; Rogiers, Aljosja; Bhaumik, Sucharita; Pans, Steven; Connor, Steve E J; Miettinen, Markku; Sciot, Raf; Tirabosco, Roberto; Brems, Hilde; Baldwin, Andrea; Legius, Eric; et al.
Abstract: Background: Neurofibromatosis 1 (NF1) leads to the development of benign and malignant peripheral nerve sheath tumors (MPNST). MPNST have been described to develop in preexisting benign plexiform neurofibromas (PN) and have a poor prognosis. Atypical neurofibromas (ANF) were recently described as precursor lesions for MPNST, making early detection and management of ANF a possible strategy to prevent MPNST. We aimed to clinically characterize ANF and identify management approaches. Methods: We analyzed clinical, imaging, and pathology findings of all patients with NF1 and ANF at 3 institutions. Results: Sixty-three patients had 76 ANF (32M/31F; median age 27.1 y). On MRI, most ANF appeared as distinct nodular lesions and were 18 F-fluorodeoxyglucose (FDG) avid. Forty-six ANF were associated with pain, 19 with motor weakness, 45 were palpable or visible, and 13 had no clinical signs. Completely resected ANF ( N = 57) have not recurred (median follow-up, 4.1 y; range, 0–14 y). Four ANF transformed into MPNST and 17 patients had a history of MPNST in a different location than was their ANF. Conclusions: Growth of distinct nodular lesions, pain, and FDG-PET avidity should raise concern for ANF in NF1. Patients with ANF are at greater risk for development of MPNST. Complete resection of ANF may prevent development of MPNST.